2020
DOI: 10.21608/ejhc.2020.110408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Sessions on Knowledge, Attitude and Self - Care Practices among Pregnant Women with Gestational Diabetes

Abstract: Background: Gestational Diabetes is associated with severe maternal, fetal and neonatal complications. Health education about regular exercises, dietary adjustment and proper taking of medication is important part in the care of women with gestational diabetes. Nurses have a significant role in educating women how to prevent and reduce gestational diabetes adverse effects on pregnancy outcomes. Aim: This study aimed to assess the effect of educational sessions on knowledge, attitude and self-care practices amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
1
0
2
Order By: Relevance
“…This result is similar with Ansarzadeh et al (2020) (29) who examined factors affecting the quality of life in women with gestational diabetes mellitus and reported that the majority of participants (73.0%) had a history of disease in their first-degree relatives. In addition, this finding is consistent with Groof et al (2019) (30) who studied prevalence, risk factors, and feto maternal outcomes of gestational diabetes mellitus in kuwait: a cross sectional study and mentioned that the women with family history of GDM were more likely to have GDM than those with no family history of GDM. Moreover, Kumari et al (2018) (31) evaluated maternal and perinatal outcome in gestational diabetes mellitus in a tertiary care hospital in delhi and reported that family history of diabetes was observed in a significantly higher number of GDM women.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result is similar with Ansarzadeh et al (2020) (29) who examined factors affecting the quality of life in women with gestational diabetes mellitus and reported that the majority of participants (73.0%) had a history of disease in their first-degree relatives. In addition, this finding is consistent with Groof et al (2019) (30) who studied prevalence, risk factors, and feto maternal outcomes of gestational diabetes mellitus in kuwait: a cross sectional study and mentioned that the women with family history of GDM were more likely to have GDM than those with no family history of GDM. Moreover, Kumari et al (2018) (31) evaluated maternal and perinatal outcome in gestational diabetes mellitus in a tertiary care hospital in delhi and reported that family history of diabetes was observed in a significantly higher number of GDM women.…”
Section: Discussionsupporting
confidence: 89%
“…Gestational diabetes leads to maternal, fetal and neonatal complications as preeclampsia, polyhydramnios, preterm labor, shoulder dystocia, infection, cesarean section, fetal demise, fetal malformation, macrosomia, hypoglycemia, hyperbilirubinemia, respiratory distress syndrome and perinatal mortality. Furthermore, in later life, other complications may develop and affect both women and their infants as obesity, type 2 diabetes mellitus, heart diseases and neuropsychological problems (4) .…”
Section: Introductionmentioning
confidence: 99%
“…O compilado de variáveis resultantes da presente amostra sobre conhecimento engloba: sintomas (HODA et al, 2018;KIM et al, 2020;EL-ANSARY;FOUAD, 2020), manejo (HODA et al, 2018;KIM et al, 2020;BHOWMIK et al, 2018), efeito maternofetal (HODA et al, 2018;BHOWMIK et al, 2018;DRAFFIN et al, 2018;MONIR;ZEBA;RAHMAN, 2018), métodos preventivos, manejo da hipoglicemia, sinais de risco materno-fetal (HODA et al, 2018), mensuração da glicemia em domicílio (HODA et al, 2018;DRAFFIN et al, 2018), frequência de mensuração da glicemia (HODA et al, 2018), seguimento da dieta (HODA et al, 2018;EL-ANSARY;FOUAD, 2020;MONIR;ZEBA;RAHMAN, 2018), atividade física (HODA et al, 2018), período de rastreamento (BHOWMIK et al, 2018), fatores de risco (EL-ANSARY; FOUAD, 2020; MONIR; ZEBA; RAHMAN, 2018), aconselhamento pré-concepção (BHOWMIK et al, 2018), possibilidade de acometimento da criança por diabetes (BHOWMIK et al, 2018), definição da doença KIM et al, 2020;EL-ANSARY;FOUAD, 2020;ANSARZADEH et al, 2020), amamentação em mães com DMG (KIM et al, 2020), lidar com o diagnóstico de DMG (DRAFFIN et al, 2018), tratamento (EL-ANSARY;FOUAD, 2020;DRAFFIN et al, 2018;MONIR;ZEBA;RAHMAN, 2018;ANSARZADEH et al, 2020), desafi...…”
Section: Conhecimentosunclassified
“…No entanto, orientações sobre os princípios gerais de uma dieta saudável não devem causar essas preocupações. Evidências como esta dão indícios da falta de conhecimento relacionada à dieta, assim como ausência de explicações claras sobre os hábitos Foi observado que mulheres com DMG acreditam que mensagens de texto como suporte e educação enviadas via SMS aumentam a satisfação com a equipe de saúde, proporcionando maior conforto sobre as formas de cuidado profissional (EL-ANSARY;FOUAD, 2020;ANSARZADEH et al, 2020). Estudo quase-experimental que explorou o efeito do modelo de ensino de intervenção na atitude de pacientes com DMG, concluiu que a ação do interventor promoveu a formação de atitudes adequadas sobre a doença e, finalmente, orientou a formação de comportamentos saudáveis das pacientes com DMG (YANG et al, 2020).…”
Section: Atitudesunclassified